Thermal conductivity and rheology of CNT nanofluids stabilized with gum arabic - Walvekar, Rashmi G. (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
A nanofluid is a suspension of nano sized particles in a base fluid. It is very much essential to know more about stability and thermal characteristics of such a nanofluid for their further use in practical applications. In the present work, Multiwalled Carbon Nanotubes (CNT) are dispersed in water. CNT dispersed in water are highly unstable and they sediment rapidly due to the Vander Waals force of attraction. Thus, to overcome this limitation Gum Arabic (GA) was added which acted as a potential dispersant. Experimental work consisting of stability studies under the effects of CNT concentration (0.01-0.1 wt%), GA concentration (0.25-5.0 wt%) and sonication time (1-24hr), respectively have been carried out. Stability was measured using UV-Vis spectrophotometer. Thermal conductivity, density and rheology of the most stable suspensions were measured as a function of temperature (25-60°C) and CNT concentration. pH of the nanofluid suspensions have also been measured. Further, convective heat transfer experiments were conducted in a laminar flow heat exchanger for CNT concentration of 0.01wt%. GA concentration and sonication time was found to play important role in dispersion of CNTs in water. Nanofluids are found to be stable at 4.0hr sonication time and the optimum GA concentration was found to be between 1.0-2.5 wt% for the range of the CNT concentration studied. Thermal conductivity was observed to be strongly dependent on temperature and CNT concentration. The enhancement in thermal conductivity was from 4.03-125.6% and 37.4-287.5% as the temperatures varied from 25- 60 °C, for 0.01wt% and 0.1wt% of CNT, respectively. CNT nanofluids showed slightly shear thinning behavior at low shear rates (<400s-1) and clear Newtonian behavior at high shear rates (400-1000s-1) and temperature. Further, viscosity was also found to be a function of CNT and GA concentration. No significant change in viscosity and density was observed in the presence of GA and CNT and the CNT nanofluid was found to be more stable in pH range between 4.5-5.5. The results on laminar flow using CNT nanofluids show increase in heat transfer coefficient up to 68-138%, which implies nanofluids as promising fluids for heat transfer application. In this study, a new model for thermal conductivity was proposed to explain the possible enhancement, by taking temperature, viscosity of the fluid, Brownian motion, shape and aspect ratio of CNTs apart from other properties of fluid and particles. The proposed model was found to be in good agreement within <10% deviation with experimental data on all CNT nanofluids available in the literature. However, the discrepancy increase as the CNT concentration increased beyond 0.06 volume fraction, which could be primary limitation of the model. Numerical simulations were carried out for 0.01, 0.04 and 0.1wt%, CNT using FLUENT by single phase approach. Numerical results are validated with the theoretical models and experimental results. The numerical results were found to be in good agreement (  10% error) with the experimental results at low CNT concentration while the deviation increased to 16% with particle concentration. In summary, CNT nanofluids are found to be more suitable for heat transfer applications in many industries due to their enhanced thermal conductivity property. This work provides large information on behavior of CNT nanofluids. The major contributions of this work includes production of stable CNT nanofluid using gum Arabic, various parameters affecting stability of the nanofluid and theoretical model for thermal conductivity.